A Rare Case of New-Onset Ulcerative Colitis following Initiation of Secukinumab - Ted George Achufusi; Prateek S. Harnee; Sekou Rawlins (Case Reports in Medicine)
Secukinumab is an IgG monoclonal antibody widely used for treatment of ankylosing spondylitis, psoriasis, and psoriatic arthritis. Recently, there has been increasing controversy regarding potential adverse effects of the drug especially in those with underlying inflammatory bowel disease. We present the case of a young male patient who developed severe new-onset ulcerative colitis following initiation of secukinumab for psoriasis, with excellent response and rapid resolution of symptoms with infliximab.